Supercapacitor applications of novel phosphorus doped graphene-based electrodes - Arvas, Melih Besir; Gursu, Hurmus; Gencten, Metin; Sahin, Yucel (ELSEVIER, 2022)
In this study, the supercapacitor performances of phosphorus-containing functional groups doped graphene electrodes, which were synthesized in one step and environmentally by Yucel's method, were investigated. The formation of graphene layers in the mesopore structure was observed by scanning electron microscopy. Functional phosphorus and phosphorus including functional groups such as -[(-P2O7)](4-) and -(PO3-) formed on the electrode surface were characterized by X-ray photoelectron spectroscopy. Cyclic voltammetry and electrochemical impedance spectroscopy were used for electrochemical characterization of the electrodes. Cyclic charge-discharge tests were also done for 1000 cycles to determine the cyclic stability of electrode materials. As the number of cycles increased during the synthesis of the electrodes, the number of different molecular functional groups on the surface increased. In addition, due to the polyphosphate structures formed on the surface, the capacity increase occurred contrary to what was expected in the cyclic charge-discharge tests of the electrodes. The highest areal capacitance was determined as 301.3 mF.cm(-2) at the current density of 10 mA.cm(-2) for P3-GE50 in sulfuric acid solution.
Keywords: P-doped graphene; P doping mechanism; Graphene supercapacitor; EDLC; Supercapacitor electrodes; CARBON NANOSHEETS; NANOWIRE ARRAYS; ELECTROCHEMICAL SYNTHESIS; FUNCTIONALIZED GRAPHENE; SHAPED SUPERCAPACITORS; POTENTIAL APPLICATION; ANODE MATERIALS; PERFORMANCE; NITROGEN; OXIDE; Energy & Fuels